PENGARUH MODEL PEMBELAJARAN LOGAN AVENUE PROBLEM SOLVING HEURISTIC TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA SMP - Erlinda Isulis Marissa; Iman Solahudin (Jurnal Edukasi dan Sains Matematika (JES-MAT), 2022)
TThe ability to solve problems is one of the abilities that students lack mastery of. This results in many difficulties faced when learning mathematics. This problem is not absolutely the student's fault. But the teacher as a facilitator also plays a very important role, one of which is the use of appropriate and efficient learning models to help improve these abilities, namely alternative choices with LAPS-Heuristics. This study aims to determine the effect of LAPS-Heuristic on the mathematical problem solving ability of SMPN 3 Kasokandel students. This study uses a mixed approach (mixed method) with data collection through test questions in the form of posttest, student response questionnaires, and documentation. The population used is two classes, namely the control and experimental classes, each of which is 24 students. The findings in this study are the LAPS-Heuristic learning model has an influence on the ability to solve mathematical problems of students by obtaining The level of problem-solving ability of the experimental class is greater than that of the control class, it can be seen from the average per indicator including indicators of knowing and understanding the problem of 90 and 71, indicators of planning problems of 80.25 and 60.5, indicators of implementing plans 87.75 and 67.25 and the indicator rechecked the results of 55.5 and 44. While the results of student responses are mostly positive with the acquisition of 90% and negative by 24%.